(±)-Peniorthoesters A and B, Two Pairs of Novel Spiro-Orthoester en-antiomers With an Unusual 1,4,6-Trioxaspi-ro[4.5]decane-7-One Unit From Penicillium minioluteum - Liu, Xiaorui; Chen, Chunmei; Zheng, Yinyu; Zhang, Mi; Tong, Qingyi; Liu, Junjun; Zhou, Qun; Wang, Jianping; Luo, Zengwei; Zhu, Hucheng; Zhang, Yonghui (Frontiers in Chemistry, 2018)
(±)-Peniorthoesters A and B (±1 and ±2), two pairs of unprecedented spiro-orthoester enantiomers with a 1,4,6-trioxaspiro[4.5]decane-7-one unit, were obtained from Penicillium minioluteum. Their structures were determined by spectroscopic methods, X-ray diﬀraction analyses, and ECD calculations. (±)-Peniorthoesters A and B are the first examples of spiro-orthoester enantiomers, and they represent the first spiro-orthoesters originating from fungi. All compounds showed potential inhibitory activities comparable to dexamethasone against NO production with IC50 values ranging from 14.2 to 34.5 μM.